THE INFLUENCE OF SERVICE QUALITY AND PERCEIVED VALUE ON CUSTOMER LOYALTY OF GARUDA INDONESIA MEMBERSHIP PROGRAM (A Study of GAMiles members’ in Malang City) - Anjarsari, Bianca Valentina (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Nowadays, the use of transportation is important in supporting the life process. Currently, the development of the aviation industry is rapidly increases, with many emerging types of airlines to meet the public demand; one of them is Garuda Indonesia that is taken as a case study for this research. This research aimed to analyze and understand the influence and relationship between service quality, perceived value, and customer loyalty within the Garuda Indonesia Membership Program. In this research, the researcher used a sample size of 200 respondents of GAMiles members, and they were collected in Malang by random sampling and a survey-based questionnaire. The research data analysis was done using Partial Least Square (PLS) with SMARTPLS application version 2.0 M3. The result indicates that both Service Quality and Perceived Value significantly influence Customer Loyalty positively, directly, and/or indirectly. By making these entire variables, customer loyalty should be increased due to the increase in service quality and perceived value. Keywords: Service Quality, Perceived Value, Customer Loyalty, GAMiles